2022
DOI: 10.1213/ane.0000000000006073
|View full text |Cite
|
Sign up to set email alerts
|

Gender Gap: A Qualitative Study of Women and Leadership Acquisition in Anesthesiology

Abstract: BACKGROUND:The representation of women among leaders in the field of anesthesia continues to trail that of their male counterparts. This qualitative study was conducted to understand the pathway of leadership acquisition among women in the field of anesthesiology. METHODS: Using constructivist grounded theory, we sought to determine whether there were specific internal or external factors that were common to women in leadership in the specialty field of anesthesiology, and specifically, how they obtained leade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…When comparing those with publicly available nomination/election process (36.8, 111/302) to those without (31.5%, 78/248), there was no difference in percentage of women leadership (P = . 19).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When comparing those with publicly available nomination/election process (36.8, 111/302) to those without (31.5%, 78/248), there was no difference in percentage of women leadership (P = . 19).…”
Section: Methodsmentioning
confidence: 99%
“…18 If the same is true in medicine, male mentors may more often encourage their male mentees to seek leadership positions. Basile et al 19 showed that early career, high-value mentorship and sponsorship were the most important factors for women in achieving anesthesiology leadership positions. In addition, having publicly available criteria and explanations of the election processes may level the playing field and increase women applicants.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%
“…Gender inequality also exists for female physicians, including anesthesiologists. Before the onset of COVID‐19, women were underrepresented in the upper leadership echelons of anesthesiology (Basile et al., 2023; Bissing et al., 2019). Although female physicians currently comprise over a third (37%) of academic anesthesiologists, only 15% of anesthesia department directors were women in 2022, according to the Association of American Medical Colleges data (Association of American Medical Colleges, 2022).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Although female physicians currently comprise over a third (37%) of academic anesthesiologists, only 15% of anesthesia department directors were women in 2022, according to the Association of American Medical Colleges data (Association of American Medical Colleges, 2022). Postulated barriers to academic advancement for female physicians include a paucity of female faculty role models and difficulty negotiating for conditions that support balancing family responsibilities and promotion requirements (Basile et al., 2023; Lane‐Fall et al., 2020). As in the corporate setting, healthcare workforce diversity is vital to improving patient care and employee engagement (Bickel et al., 2002; Cohen et al., 2002; Gomez & Bernet, 2019; Leslie et al., 2017).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…1 Such documentation focuses on quantifying underrepresentation, but does not shed light on strategies that might be used to mitigate the low numbers of women in the upper echelons of academic medicine. In this issue of Anesthesia & Analgesia , Basile et al 2 report the findings of 26 semistructured qualitative interviews conducted with women leaders in academic anesthesiology. The authors focused their interviews on respondents’ personal qualities and perceived barriers and facilitators to advancement into leadership roles to identify common factors that contributed to individual success.…”
mentioning
confidence: 99%